Autoethnographic Reflections on Da’wah Representation in Rindu Suara Adzan 2024 - Budi Zaelani (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2025)
The Rindu Suara Adzan 2024 religious-comedy soap opera depicts quotidian socioeconomic realities infused with Islamic principles, including humor and elements of contemporary culture. This article offers an autoethnographic reflection on the author's experience portraying